A software design tool for microwave radio - Ashraf Gasim Elsid Abdalla; Mahamod Ismail; Ahmad Faizal WM. Zain (1997)
This paper deals with wave propagation calculation and cost optimization software development for microwave radio. The software presents a design tool for line of sight link planning. The main cost factor in a microwave network depends on tower structure and antenna heights. Antenna heights are normally chosen to overcome the first Fresnel zone obstruction. A software tool for the analysis and evaluation of a single microwave relay link has been developed. In addition, cost optimization method for a microwave radio network involving more than two antennas has been developed. This paper includes calculations and analysis of the geographical data in the chosen area in order to determine the effective earth's radius to achieve better optimization. In addition, terrain profile generation and microwave point-to-point link calculation was considered